Peningkatan Aktivitas dan Hasil Belajar Matematika Siswa Melalui Penerapan Metode Pembelajaran Team Quiz - Yuntawati Yuntawati; Lalu Abdul Aziz (Jurnal Pacu Pendidikan Dasar, 2022)
This research is based on students' learning completeness which is still low, lack of enthusiasm of students in expressing opinions during the learning process, especially in providing feedback on the problems given by the teacher. The purpose of this study is to describe the steps of the Team Quiz learning method so that it can improve the activities and results of learning mathematics of class VIII students of MTs Al-Raisiyah Sekarbela Mataram. The type of research used is classroom action research (CAR) which consists of two cycles, where each cycle consists of four stages, namely the stages of planning, action, observation, and reflection. The instruments used were in the form of activity observation sheets and evaluation tests. The results obtained were analyzed by percentage formula. Based on the results of the analysis that has been carried out, the results of the student questionnaire obtained at the first meeting of the first cycle were 43.06% and the results of the student questionnaire were obtained at the second meeting of the first cycle of 48.61%. In the second cycle the results of the student questionnaire were obtained at the first meeting of the second cycle of 68.06% and the results of the student questionnaire were obtained at the second meeting of the second cycle of 77.78%. Both of these values ​​indicate that students in the category are quite active in the first cycle and the active category in the second cycle. Furthermore, for evaluation of learning outcomes in the first cycle obtained classical completeness of 63.63% with the number of students who did not complete is 8 people out of a total of 22 students, while in the second cycle there was an increase in learning outcomes where classical completeness was 86.36%, with the number of students not complete decreased to 3 people out of a total of 22 students. Based on the results that have been obtained, it can be concluded that the application of Team Quiz learning methods can improve the activities and results of learning mathematics of class VIII MTs Al-Raisiyah Sekarbela Mataram academic year 2018/2019.